Infrastructure Operations Strategies That Affect the Efficiency of Public Service of Berkprai Subdistrict Municipality Ban Pong District Ratchaburi Province - Suwannapruek, Teerasak; Nikornpttaya, Saowaluk; Ingun, Rungsun (Journal of Graduate MCU KhonKaen Campus, 2023)
The objective of this study were 1) To study the level of implementation according to the infrastructure strategy of Berkprai subdistrict municipality Ban Pong District Ratchaburi. 2) To study the level of public service efficiency of Berkprai subdistrict municipality Ban Pong District Ratchaburi. 3) To study the strategies of infrastructure operations that affect the efficiency of public services of Berkprai subdistrict municipality Ban Pong District Ratchaburi. and 4) To study the recommendations to increase the efficiency in the implementation of the strategy of Berkprai subdistrict municipality Ban Pong District Ratchaburi. Collected data by questionnaires with 376 household representatives of Berkprai subdistrict municipality. Multistage randomization, hierarchical randomization and simple randomization. Descriptive statistics and multiple regression-type reference statistics were used. The study found 1) The level of implementation according to the infrastructure strategy of Berk Phrai subdistrict municipality were high level. 2) The public service efficiency level of Berkprai subdistrict municipality were high level. 3) Infrastructure operations strategy development of public electrical systems and development of traffic systems affected the efficiency of public service Berkprai subdistrict municipality. and 4) Berkprai subdistrict municipality should provide information about the procedures for contacting government officials, create channels to provide information and receive information from people in a variety of channels, provide knowledge of local law, One stop service system and provide comprehensive information.